IMPLEMENTASI VIRTUAL PRIVATE NETWORK OVER GRE TUNNEL - Taufik Rahman (LPPM Nusa Mandiri, 2017)
VPN network is very interesting to be discussed and widely so that many have done research then this research will do the implementation of VPN network using GRE Tunnel technology. This research will answer how this virtual interface can connect more than one router with another router by using GRE protocol to deliver packets, protocols and more so that user needs such as connecting layer 2 between sites can be fulfilled through VPN GRE Tunnel. Finally after the preparation for this research started to install simulator GNS3, Mikrotik RouterOS, VirtualBox, operating system. Network administration by writing an ip address. Configuration on a loopbaack adapter, MikroTik-HeadOffice, MikroTik-Branch, and Pc-Branch. Once connected is formed a virtual interface and given IP address as ip binder of two public ip. Then proved by ping and tracert between Pc-Branch can be interconnected, so can also exchange data with sharing files so that can be done mapping drive. With Packet Sniffer and Torch tools on Mikrotik can see traffic passing through the virtual GRE tunnel interface. After experimenting with the GNS3 simulator application in such a way with the console script and proven with the image that the VPN network with GRE tunnel interface can connect more than 2 MikroTik-Branch routers through MikroTik-HeadOffice as the network backbone. With its built VPN GRE tunnel network, the data communication is safe because it is inside the tunnel even in the internet network. Further research, combining GRE Tunnel with others.